Educational needs of women in relation to postpartum religious orders - Marjan Beigi; Nafisehsadat Nekuei (Wolters Kluwer Medknow Publications, 2017)
Introduction: Religious orders are one of the educational needs of the postpartum period. This study was conducted to determine the educational needs of postpartum religious orders.Materials and Methods: This cross-sectional study was conducted among 421 postpartum women and 15 specialists. Quota random sampling was conducted from January to March 2014 in Isfahan, Iran. Data analysis was performed using the Statistical Package for the Social Sciences software and statistical methods.Results: From the perspective of women and specialists, the results showed that the educational needs of women in postpartum religious orders is high.Conclusion: Considering the high educational need in the field of postpartum religious orders, it is necessary to integrate education in prenatal and postnatal health education programs.